STRATEGY ANLYSIS OF VILLAGE OWNED BUSINESS ENTITIES (BUMDES) IN IMPROVING THE COMMUNITY’S ECONOMY IN THE VILLAGE OF MADDANRENG PULU SUB-DISTRICT PATIMPENG - asdar saputra (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This study aims to determine the strategy of Village Owned Enterprises (BUMDes) in improving the economy of the community in Maddanreng Village, Patimpeng Pulu District, Bone Regency. The population in this study were the community and the management of Village Owned Enterprises (BUMDes) Maddanreng Village, Patimpeng Pulu District, Bone Regency. The data collection techniques are carried out by literature, documents, interviews and observations. Data analysis techniques are reduction, data presentation and conclusion drawing. The results of the study show that: 1) The presence of BUMDes has made it easier for the people of Maddanreng Pulu Village, especially the farmers in the village, whose harvests they used to harvest sometimes often fail due to lack of knowledge to deal with pests, now they can harvest better than previous years. Because of the socialization and training on pests provided by the BUMDes management on how to choose seeds and plant them properly in order to produce good quality. 2) The role of BUMDes has proven to be very good, this can be seen from its role in providing easy access for the community to obtain business capital. with a very easy procedure and also eased because of the gradual payment system. So that it can overcome poverty in Maddanreng Pulu village even though this BUMDes Maddanreng Pulu has only been operating for 2 years and only has several business units and savings a